The problems of the use of food additives in the infant’s foodstuffs (Environment & Health, 2019)
The article presents the data on the use of food additives in the infant’s food intakes, their classification, effects on the organism, measures for the prevention of negative impact.Objective: We analysed the research data on the use of food additives in the food intakes of the infants.Materials and methods: We analyzed the data of the scientific research on the use of food additives in the nutrition of the infants.Results: Nutritional additives are widely used throughout the world but the number of special foods for the children allowed for the manufacture for the children is significantly limited, especially in dyes, flavors, sweeteners, and sugar substitutes.Conclusions: There is no effective control of the production and use of food additives, especially in the manufacture of the infant’s food in Ukraine until now. Separate inspections do not allow a full guarantee of the fulfillment of approved standards by the manufacturers and a complete elimination of the situations where they may use prohibited food additives.
Keywords: children; infant’s food; food additives; special foodstuffs